Synthesis and Magnetic Characterization of (Porous Silicon/"Hard-Soft" Magnetic) Nanocomposites. (19th August 2016) - Rumpf, Klemens; Granitzer, Petra; Michor, Herwig; Poelt, Peter
Abstract : The purpose of this work is to combine magnetic nanostructures of two different metals within porous silicon to influence the magnetic switching behavior of this porous silicon/metal nanocomposite. These "hard/soft" magnetic nanocomposites have been achieved by two different routes. Porous silicon templates in the mesoporous regime have been employed for the electrochemical incorporation of different types of magnetic nanostructures. Two kinds of porous silicon templates have been used, on the one hand double sided porous silicon which has been achieved by etching of an ultrathin wafer in a double tank cell and on the other hand a silicon wafer has been porosified on one side only. The double-sided porous silicon has been filled with Ni on one side and with Co on the other side, also using a double tank cell. In the case of the one-sided sample both metals have been electrochemically deposited alternatingly inside the pores.